Pengelolaan Model Pembelajaran Kooperatif Tipe STAD (Student Team-Achievement Divisions)Pada Kelas VI SD Negeri 01 Tanjungsari Kabupaten Pemalang - Suwardi, Pipit; , Prof. Dr. Bambang Sumardjoko; , Dr. Samino, M.M (2015)
This study aims to: (1) describe the planning of cooperative learning model type STAD in class VI SD Negeri 01 Tanjungsari. (2) describe the implementation process of learning using cooperative learning model type STAD in class VI SD Negeeri 01 Tanjungsari. (3) describe how to evaluate the cooperative learning model type STAD in class VI SD Negeri 01 Tanjungsari. This research is qualitative. Implementation of research in SD Negeri 01 Tanjungsari Pemalang, especially the sixth grade. Informants in this study is the principal, teacher of sixth grade, sixth grade students, and the parties concerned to support the research data. Data collection techniques by means of in-depth interviews, observation and documentation. The validity of the data using the extension of participation, triangulation and peer examination through discussion. Data were analyzed using data reduction, the data display and conclusion. The results of this study: in planning, preparing teachers syllabus and lesson plans. The more mature teacher in planning the start of the lesson plan, syllabus and media to be used, the more likely the teachers succeeded in conveying the material. In practice, STAD cooperative learning is done by the class teacher VI consists of five main components, namely the presentation of classes, study groups, quizzes, balanced development and group awards. In the evaluation, the teacher prepares the test description in measuring the ability of each student. She also has conducted remedial for students whose value has not reached minimal completeness criteria, as well as provide enrichment for students whose value has reached minimal completeness criteria. Keywords: management, learning, STAD